Histomorphometric evaluation of bone regeneration using autogenous bone and beta-tricalcium phosphate in diabetic rabbits - Živadinović Milka; Andrić Miroslav; Milošević Verica; Manojlović-Stojanoski Milica; Prokić Branislav; Prokić Bogomir; Dimić Aleksandar; Ćalasan Dejan; Brković Božidar (Vojnosanitetski Pregled)
Background/Aim. The mechanism of impaired bone healing in diabetes mellitus includes different tissue and cellular level activities due to micro- and macrovascular changes. As a chronic metabolic disease with vascular complications, diabetes affects a process of bone regeneration as well. The therapeutic approach in bone regeneration is based on the use of osteoinductive autogenous grafts as well as osteoconductive synthetic material, like a β-tricalcium phosphate. The aim of the study was to determine the quality and quantity of new bone formation after the use of autogenous bone and β-tricalcium phosphate in the model of calvarial critical-sized defect in rabbits with induced diabetes mellitus type I. Methods. The study included eight 4-month-old Chincilla rabbits with alloxan-induced diabetes mellitus type I. In all animals, there were surgically created two calvarial bilateral defects (diameter 12 mm), which were grafted with autogenous bone and β-tricalcium phosphate (n = 4) or served as unfilled controls (n = 4). After 4 weeks of healing, animals were sacrificed and calvarial bone blocks were taken for histologic and histomorphometric analysis. Beside descriptive histologic evaluation, the percentage of new bone formation, connective tissue and residual graft were calculated. All parameters were statistically evaluated by Friedman Test and post hock Wilcoxon Singed Ranks Test with a significance of p < 0.05. Results. Histology revealed active new bone formation peripherally with centrally located connective tissue, newly formed woven bone and well incorporated residual grafts in all treated defects. Control samples showed no bone bridging of defects. There was a significantly more new bone in autogeonous graft (53%) compared with β-tricalcium phosphate (30%), (p < 0.030) and control (7%), (p < 0.000) groups. A significant difference was also recorded between β-tricalcium phosphate and control groups (p < 0.008). Conclusion. In the present study on the rabbit grafting model with induced diabetes mellitus type I, the effective bone regeneration of critical bone defects was obtained using autogenous bone graft. [Projekat Ministarstva nauke Republike Srbije, br. 175021]